Pengaruh Pinjaman Online Terhadap Perilaku Konsumtif Mahasiswa Perbankan Syariah Kota Pekanbaru - Niken Damayanti; Fitri Fitri; M. Syahrullah (EL-EMIR Institute, 2025)
The development of financial technology (fintech) has introduced online loan services that facilitate access to cash, including among students. While offering convenience and speed of disbursement, online loans have the potential to encourage student consumer behavior, leading to serious financial risks. This study aims to examine the influence of online loan use on the consumer behavior of students in the Islamic Banking Study Program in Pekanbaru City. The method used was quantitative, with a simple random sampling technique involving 81 respondents from a population of 442 students using online loans. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression analysis and classical assumption tests. The results showed a positive and significant influence of online loan use on student consumer behavior. These findings suggest that the ease of access and short process of online loans encourage students to engage in irrational and wasteful consumer behavior. Therefore, financial literacy education and strict regulations are urgently needed to reduce the risk of problem debt and foster healthy consumption patterns among students.